The influence of global and local iconic brand positioning on advertising persuasion in an emerging market setting - Heinberg, Martin; Ozkaya, H Erkan; Taube, Markus (Journal of International Business Studies, 2017)
This study explores how positioning a brand as global and/or local iconic can moderate the impact of advertising frequency (AF) on brand attitudes in an emerging market context. We argue that brands may be seen as the source of an advertisement and that the positioning of a brand can thus enhance source attractiveness, and/or source credibility, which in turn facilitate the impact of AF on brand attitudes. Our results support that both a global and a local iconic positioning enhance the AF–brand image relationship, but they do not have an effect on the AF–brand quality relationship. Additionally, we examine whether source attractiveness and source credibility mediate these moderation effects and find that only source attractiveness is a significant mediator. Additionally, we investigate whether a hybrid positioning strategy (i.e., positioning as both global and local iconic) is beneficial. Results indicate that a separate positioning (i.e., global or local iconic) is a better strategy to increase the attractiveness of the advertising source and in turn facilitate the effect of advertising frequency to create brand image.